Optical Fiber Tip Fabricated by Improved Turner Method - Wang, Z.F.; Li, C.X. (Asian Journal of Chemistry, 2013)
Near-field scanning optical microscopy probes are produced by improved Turner method. The geometrical shapes, surface roughness and cone angle are compared. Better near-field scanning optical microscopy probes with smooth surface and larger cone angle (up to 50-70º) are fabricated by our improved Turner method, which is carried out with simply etching dress after adopting classic Turner.